Фолікулярні утворення щитоподібної залози: класификація та цитологічні критерії - Гузь, О. О.; Белемець, Н. І. (Clinical Endocrinology and Endocrine Surgery, 2011)
The lecture discussed the cytological criteria for classification and clinical application of FNA results in the differential diagnosis of follicular thyroid formation.